PUTUSAN BEBAS TERHADAP TINDAKAN S SELAKU PENGENDARA MOBIL PEMADAM KEBAKARAN YANG MENYEBABKAN KECELAKAAN DAN HILANGNYA NYAWA ORANG LAIN DITINJAU DARI UNDANG-UNDANG NOMOR 22 TAHUN 2009 (TENTANG LALU LINTAS & ANGKUTAN JALAN) DAN AGAMA - Cynthia Novia Johansyah (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2020)
Abstract - This study is intended to analyse the actions carried out by the perpetrator (S) who when carrying out his position as a firefighter, named S driving a fire engine car but because of his inattention causing traffic accidents that cause death can be subject to Article 310 paragraph (4) Law number 22 of 2009 concerning Road Traffic and Transportation Keywords: traffic accidents, firefighters, Law No. 22 of 2009 concerning Road Traffic and Transportation, the Criminal Code.